Economic evaluation of a combined screening and stepped-care treatment program targeting psychological distress in patients with metastatic colorectal cancer: A cluster randomized controlled trial. (July 2020) - El Alili, Mohamed; Schuurhuizen, Claudia S.E.W; Braamse, Annemarie M.J.; Beekman, Aartjan T.F.; van der Linden, Mecheline H.; Konings, Inge R.; Dekker, Joost; Bosmans, Judith E.
Background: Psychological distress is highly prevalent among patients with metastatic colorectal cancer. Aims: To perform an economic evaluation of a combined screening and treatment program targeting psychological distress in patients with metastatic colorectal cancer in comparison with usual care. Design: Societal costs were collected alongside a cluster randomized controlled trial for 48 weeks. A total of 349 participants were included. Setting: Participants were recruited from oncology departments at 16 participating hospitals in the Netherlands. Methods: Outcome measures were the Hospital Anxiety and Depression Scale and quality-adjusted life-years. Missing data were imputed using multiple imputation. Uncertainty was estimated using bootstrapping. Cost-effectiveness planes and cost-effectiveness acceptability curves were estimated to show uncertainty surrounding the cost-effectiveness estimates. Sensitivity analyses were performed to check robustness of results. Results: Between treatment arms, no significant differences were found in Hospital Anxiety and Depression Scale score (mean difference: –0.058; 95% confidence interval: –0.13 to 0.011), quality-adjusted life-years (mean difference: 0.042; 95% confidence interval: –0.015 to 0.099), and societal costs (mean difference: –1152; 95% confidence interval: –5058 to 2214). Cost-effectiveness acceptability curves showed that the probability of cost-effectiveness was 0.64 and 0.74 at willingness-to-pay values of €0 and €10, 000 per point improvement on the Hospital Anxiety and Depression Scale, respectively. The probability that the intervention was cost-effective compared to usual care for quality-adjusted life-years was 0.64 and 0.79 at willingness-to-pay values of €0 and €20, 000 per quality-adjusted life-year, respectively. Conclusion: The intervention is dominant over usual care, primarily due to lower costs in the intervention group. However, there were no statistically significant differences in clinical effects and the uptake of the intervention was quite low. Therefore, widespread implementation cannot be recommended.